2012
DOI: 10.1371/journal.pone.0038929
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Lineage Influenza B and Heterologous Influenza A Antibody Responses in Vaccinated Mice: Immunologic Interactions and B/Yamagata Dominance

Abstract: The annually reformulated trivalent inactivated influenza vaccine (TIV) includes both influenza A/subtypes (H3N2 and H1N1) but only one of two influenza B/lineages (Yamagata or Victoria). In a recent series of clinical trials to evaluate prime-boost response across influenza B/lineages, influenza-naïve infants and toddlers originally primed with two doses of 2008–09 B/Yamagata-containing TIV were assessed after two doses of B/Victoria-containing TIV administered in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 36 publications
(42 reference statements)
5
33
0
5
Order By: Relevance
“…In this present study, no amino acid change was detected in the main antigens (either HA or NA) of influenza cell seed viruses after three passages in suspension MDCK cells. However, a mutation that already existed in egg seed viruses as previously discussed has been maintained in cell seed viruses (Skowronski et al, 2012). These results are in agreement with previous observations that propagation of influenza viruses in mammalian cells may induce less mutation than that in eggs (Suphaphiphat et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this present study, no amino acid change was detected in the main antigens (either HA or NA) of influenza cell seed viruses after three passages in suspension MDCK cells. However, a mutation that already existed in egg seed viruses as previously discussed has been maintained in cell seed viruses (Skowronski et al, 2012). These results are in agreement with previous observations that propagation of influenza viruses in mammalian cells may induce less mutation than that in eggs (Suphaphiphat et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…No change was observed in the amino acid sequence of either HA or NA of all three cellpassaged viruses after three passages in suspension MDCK cells. B/Brisbane/60/2008 had one mutation (N212S) in HA compared to the reference wild-type strain; however, this mutation already existed in the candidate vaccine virus obtained from NIBSC as previously discussed (Skowronski et al, 2012). This mutation, which may result from egg adaptation, did not induce any reversion after propagation three times in MDCK cells.…”
Section: Genetic Stability Of Seed Virusesmentioning
confidence: 79%
“…Interestingly, in the Skowronski study, also the A/H1N1/Brisbane/59/2009 strain was included. They demonstrated that the immunogenicity against the A/H1N1/Brisbane strain was relatively poor in contrast to the compared A/H1N1/California/7/2009 strain that also was included in the study [38]. Thus in this study, our nasal TIV vaccine candidate (with Endocine™ or N3OA) obtained fair humoral IgG immune responses towards all three influenza strains (A/H1N1/Brisbane/59/2007, A/H3N2/Brisbane/10/2007 and the B/Brisbane/60/2008) in comparison to what was obtained with the TIV given parentally.…”
Section: Discussionmentioning
confidence: 99%
“…The potency of all three vaccine strains of the post-expiry but cold-chain maintained 2008-09 Fluviral lot that was used was confirmed by single radial immuno-diffusion (SRID) testing by the Center for Biologics Evaluation and Research, United States (US) Food and Drug Administration (FDA) [21]. US specifications require $27 mg/mL hemagglutinin (HA) for each antigen (dose 0.5 mL) based on the mean of three tests, with additional requirements around the standard deviation (SD).…”
Section: Interventionmentioning
confidence: 97%